Dynamic angular velocity turning for extremum seeking control of a two-dimensional mobile robot with external disturbances. (7th June 2019) - Wang, Yibin; Li, Huilin; Sun, Xiaoying; Chen, Hua
In this article, the extremum seeking control of a two-dimensional mobile robot with external disturbances is discussed by applying dynamic angular velocity turning method. First, the extremum seeking scheme is proposed to describe the trajectory of the two-dimensional robot and to achieve extreme value optimization through dynamic feedback. Secondly, the method of finite-time control and dynamic feedback is proposed to ensure that the dynamic angular velocity converges to the virtual controller within a finite time. Thirdly, the sliding mode disturbance observer is designed to guarantee that the observer converges to an unknown disturbance in finite time. Furthermore, we allow the averaging method and the results are applied in stability analysis. Finally, our control scheme is feasible by a series of simulations.